Perception of Lexical Neutral Tone Among Adults and Infants - Fan, Shanshan; Li, Aijun; Chen, Ao (Frontiers in Psychology, 2018)
Neutral tone (T0) is a special tone form in Mandarin that contains tonal and stress information. Compared with canonical tones, T0 has a much shorter duration and reduced pitch contour. Its tonal contour is determined by the preceding canonical tone. However, not much is known about the perception of tonal and stress information in T0. In the current study, we investigate (1) whether T0 can be perceived as lexically unstressed by stress-language listeners; and (2) how Mandarin (tone language)- and Dutch (stress language)-learning infants perceive T0. Three experiments were conducted. In Experiment 1, Dutch adults identified T0 as unstressed when presented with disyllabic sequences ending in T0. In Experiment 2, we used the visual fixation paradigm to test 4- to 6-month-old and 10- to 12-month-old Dutch and Mandarin infants on pseudoword discrimination (/pan1san4/ [high-level + high-falling] and /pan1san0/ [high-level + mid-falling]). T4 and T0 each exhibit a similar falling contour. The results show that (1) after being habituated to neutral tone sequences (/pan1san0/), Dutch infants discriminated the T1T0-T1T4 contrast; and (2) neither age groups of Mandarin infants discriminated the tone contrast. Assuming Mandarin infants' lack of discrimination might be due to the similar F0 contours, we tested Mandarin infants in Experiment 3 using a more salient contrast, /pan1san2/ (high-level + mid-rising) and /pan1san0/. While no overall discrimination was observed, those who were habituated to /pan1san0/ demonstrated discrimination. The continuous discrimination of Dutch infants suggests that they might process neutral-canonical tone contrast as lexical stress rather than as tonal information. Overall, Mandarin infants' failure implies that the representation of T0 is not complete during their first year of life; the acquisition of tonal categories may therefore take longer than we expected.